Pengaruh Budaya Organisasi terhadap Kinerja Pegawai di Kantor Kelurahan Wiringpalenae, Kecamatan Tempe, Kabupaten Wajo - Amrizal Akmul; Sofyan Marzuki; Amiluddin Amiluddin (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
In an organization, human resources are the main asset that plays an important role in achieving organizational goals. One of the factors that affect the effectiveness of employees' work is organizational culture. Organizational culture reflects the values, norms, and habits that are embraced by the same and serves as a code of behavior for all members of the organization. A strong and positive culture can create a conducive work environment, improve work morale, as well as encouraging employee loyalty and productivity. Conversely, a culture that is not aligned with organizational goals can lower motivation and negatively impact performance. Therefore, it is important to understand the extent to which organizational culture affects employee performance. In general, this study aims to analyze the extent to which organizational work culture affects employee performance in the Wiringpalennae Village Office, Tempe District, Wajo Regency The purpose of this study is to assess how good the Organizational Culture is to Employee Performance in the Wiringpalennae Village Office, Tempe District, Wajo Regency, as well as to measure the influence of Organizational Culture on Employee Performance in the Wiringpalennae Village Office, Tempe District, Wajo Regency. The research method applied is quantitative associative. The research sample involved 19 respondents. Data was collected through questionnaires or questionnaires and data analysis was carried out using quantitative descriptive analysis techniques, associative analysis, and simple linear regression analysis. The findings in the study stated that Organizational Culture has a positive and significant influence on Employee Performance at the Wiringpalennae Village Office, Tempe District, Wajo Regency. The analysis also shows that the Organizational Culture at the Wiringpalennae Village Office, Tempe District, Wajo Regency is in the good category, and the Performance of Employees at the Wiringpalennae Village Office, Tempe District, Wajo Regency is in the very good category.